A Review on Bioethanol Production through the Valorization of Food Waste in Indonesia - Trisna, Tifara Elaine; Jai, Jyotsna; Shirleen, Deborah; Matthew, Ryan; K, Katherine (Indonesia International Institute for Life Sciences, 2022)
Biofuels are one of the numerous alternatives that are currently being considered to replace fossil fuels as it is more environmentally friendly. Specifically, bioethanol is often thought as a better alternative to gasoline fuel as it is considered cleaner, more renewable, and greener as it is synthesized from renewable feedstock which contributes to the reduction of greenhouse gas emissions to the environment. As bioethanol is produced from carbohydrate and starch rich food crops, food waste (FW) poses a potential source for bioethanol production as it is especially rich in carbohydrates and lipids. Bioethanol production itself consists of several steps which includes food waste selection, pretreatment, saccharification and fermentation, and recovery. Cafeteria FW was reviewed to be the best type of FW for bioethanol production as it has the highest carbohydrate and starch content. Subsequently, acid pretreatment was considered to be the best method due to low cost, high yielding, and time efficient method. Moreover, the non-isothermal simultaneous saccharification and fermentation (NSSF) produces 1.42 g ethanol/L.h with a time of 38 hours. Lastly, the enzyme-assisted extraction technique is most preferred to recover the bioactive compounds as it led to the highest yield of product (94%) compared to other methods.